PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP REAKSI INVESTOR - Apriliastuti, Apriliastuti; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test the influence of financial performance and firm size to the reaction of investors. The samples are 60 companies which have been selected by using purposive sampling from the manufacturing companies of Food and Beverages sector which are listed in Indonesia Stock Exchange during the 6 years period from 2008 to 2013. The financial statement of the company and Composite Stock Price Index (IHSG) has been obtained from the Indonesia Stock Exchange Gallery. Meanwhile, the financial ratio and the stock price data have been obtained from the Indonesian Capital Market Directory and www.duniainvestasi.com. The classic assumption test and the multiple regressions analysis have been done by using SPSS statistic test version 20.0. The result of this research shows that the regressions models of this research do not have any heteroscedasticity, multicollinearity, and autocorrelation symptoms and the data has been normally distributed. The result of multiple analysis shows that Current Ratio (CR), Dept to Equity Ratio (DER), Return on Assets (ROA), Price Earnings Ratio (PER), and firm size do not have any significant influence to the Cumulative Abnormal Return (CAR). Meanwhile, Total Assets Turnover (TAT) has significant influence to the Cumulative Abnormal Return (CAR).Keywords: Financial Performance, Firm Size, and Investorsâ Reaction (Cumulative Abnormal Return).